2005
DOI: 10.1098/rspb.2005.3287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of density dependence on predator–prey seabird interactions at large spatio-temporal scales

Abstract: Theoretical investigations of competitive dynamics have noted that numbers of predator and prey influence each other. However, few empirical studies have demonstrated how a life-history trait of the prey (such as fecundity) can be affected simultaneously by its own density and the density of predators. For instance, density dependence can reduce fecundity with increasing number of prey, while inverse density dependence or Allee effects may occur especially when the prey is a social organism. Here we analysed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 31 publications
(49 reference statements)
0
50
0
Order By: Relevance
“…Previous studies have found evidence that social stimulation from an increased number of conspecifics can facilitate earlier onset of breeding (Coulson 2002), so we a priori predicted that, if laying date is related to breeding density, the effect will be positive. Although population size may have negative as well a positive effects on demographic parameters (Greene & Stamps 2001, Oro et al 2006, because of the highly social nature of guillemot colonies, we considered only the positive effects of population size.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found evidence that social stimulation from an increased number of conspecifics can facilitate earlier onset of breeding (Coulson 2002), so we a priori predicted that, if laying date is related to breeding density, the effect will be positive. Although population size may have negative as well a positive effects on demographic parameters (Greene & Stamps 2001, Oro et al 2006, because of the highly social nature of guillemot colonies, we considered only the positive effects of population size.…”
Section: Methodsmentioning
confidence: 99%
“…As third covariate we consider the ratio of fish catches to the total number of breeding pairs of Audouin's gulls and of the sympatric yellow-legged gulls, L. michahellis (Oro et al 2006). The two species compete for similar resources as shown by the high degree of overlap in the diet and breeding habitat (Martínez-Abraín et al 2003, Oro et al 2006. The fourth covariate consider was the North Atlantic oscillation index (NAO hereafter, Hurrell 1995) taken as a measure of winter conditions.…”
Section: Hypotheses and Covariatesmentioning
confidence: 99%
“…Large opportunistic species (e.g. gulls, giant petrels) can be facultative predators on smaller seabird species within the community, and population increases of the former following the appearance of large amounts of food from human activities may increase the predation rates on vulnerable species (Regehr & Montevecchi 1997, Votier et al 2004, Oro et al 2006a. Seabirds may also more or less share parasites and pathogens that are prevalent in their breeding habitat, although the interactions involved are likely complex.…”
Section: Population Dynamicsmentioning
confidence: 99%
“…Although predatory interactions among seabird species are less well studied than competitive interactions, they do occur (Gilchrist 1999, Votier et al 2004, Oro et al 2006a, Oro & Martínez-Abraín 2007. Large opportunistic species (e.g.…”
Section: Population Dynamicsmentioning
confidence: 99%